Euryalid brittle stars from the International Indian Ocean Expedition 1963–64 (Echinodermata: Ophiuroidea: Euryalida) - Baker, Alan N.; Okanishi, Masanori; Pawson, David L. (Zootaxa, 2018)
Fourteen species of euryalids are reported from collections made in the eastern and western Indian Ocean during the International Indian Ocean Expedition. Three new species are described: Astrocladus goodingi from the Comoro Islands, Astrocladus socotrana from the northwestern Indian Ocean near the island of Socotra, and Astrocyclus somaliensis from off northeastern Somalia. Range extensions are documented for Asteronyx luzonicus, Astroglymma sculptum, Astrocladus ludwigi, Asteromorpha capensis and Squamophis amamiensis.